Back Cover: Insights into the Biosynthesis of Dehydroalanines in Goadsporin (ChemBioChem 3/2016). Issue 3 (3rd February 2016) - Ozaki, Taro; Kurokawa, Yukari; Hayashi, Shohei; Oku, Naoya; Asamizu, Shumpei; Igarashi, Yasuhiro; Onaka, Hiroyasu
Abstract : The back cover picture shows a paper disk diffusion assay of goadsporin against Streptomyces lividans TK23 on an agar plate. Through the inactivation of godF and godG, goadsporin B and goadsporin C were identified. The structures of these compounds provide insights into the mechanism of dehydroamino acid formation catalyzed by LanB‐type enzymes. More information can be found in the communication by H. Onaka et al. onpage 218 in Issue 3, 2016 (DOI:10.1002/cbic.201500541 ).